Mesoporous carbon as an effective support for Fe catalyst for CO2 hydrogenation to liquid hydrocarbons. Issue 37 (April 2020) - Hwang, Sun-Mi; Zhang, Chundong; Han, Seung Ju; Park, Hae-Gu; Kim, Yong Tae; Yang, Sunkyu; Jun, Ki-Won; Kim, Seok Ki
Highlights: Mesoporous carbon-supported FeK catalyst convert CO2 into liquid fuel. Fe carbide phases are easily formed on mesoporous carbon support. Mesoporous carbon support is beneficial to the dissipation of heavy products in the pore. Abstract: Identifying highly efficient catalysts for direct CO2 hydrogenation to liquid hydrocarbons is crucial for CO2 utilization via chemical conversion using renewable resources, the so-called Power-to-Liquids. In this study, well-defined mesoporous carbon (MPC) of 6.9 nm pore size was synthesized as a support material for Fe oxycarbide nanoparticles, which serve as active sites for the CO2 hydrogenation reaction, combining reverse water-gas shift and Fischer-Tropsch reactions. The unique physicochemical properties of MPC favored the formation of an active carbidic Fe phase and the rapid diffusion of produced hydrocarbons which resulted in an enhanced CO2 conversion and long-chain hydrocarbon selectivity. As a result, the MPC supported Fe catalyst showed C5+ hydrocarbon selectivity of 44.5% with a CO2 conversion rate of 50.6% (300 °C, 2.5 MPa, H2 /CO2  = 3).